Muscle strength of the upper extremity in professional tennis players; evaluation and comparison with players at club level - Montalvan, B.; Cousteau, J. P.; Gires, A.; Delery, B.; Ceccaldi, C.; Kahlard, P.; Gaslone, M. (1999)
Tennis elbow is common among players at club level, but is rarely encountered in professional tennis players. Several authors have proposed the hypothesis of an ideal division of the muscular strength of the wrist and arm. The attractive theory offers the possibility of curative and preventative re-education. In order to test this hypothesis, researchers studied the isokinetic muscle strength of the wrist and elbow in 15 professional tennis players and 15 club level players. The investigations were performed in the medical unit of the national training center of the French Tennis Federation between November 1998 and 30 April 1999. All players were tested by the same investigator, in the same position, on a rotating dynamometer Cybex 340. The muscle groups tested were the flexors (60 and 180°/s), extensors (60 and 180°/s), pronators (60 and 150°/s) and supinators (60 and 150°/s) of the wrist, and the elbow flexors (120 and 240°/s) and extensors (120 and 240°/s). The players had never had any pain in their dominant wrist and elbow. There were no significant differences in dominant wrist strenght measured at two different velocities in the flexors, extensors, pronators and supinators. The flexion/extension and supinator/pronator ratios were the same at the dominant side in the two groups. The professional tennis players were significantly stronger in elbow extension at 240°/s, and were slightly, but not significantly, stronger at 120°/s. No significant differences between the two groups were found in elbow flexion strength. The flexion/extension ratio in the two groups was identical. In conclusion, there were no significant differences between professional and club level tennis players. At the elbow level, the muscle strength of the triceps was increased at high velocities, probably related to the power of the serve in professional tennis players. No evidence was found of a particular division of muscle strength at the level of the wrist, with a protective character for ennis elbow.